Choeropsis liberiensis (Artiodactyla: Hippopotamidae). (6th December 2019) - Flacke, Gabriella L; Decher, Jan
Abstract: Choeropsis liberiensis (Morton, 1849), commonly called the pygmy hippopotamus or pygmy hippo, is the only extant species in the genus Choeropsis . A solitary, forest-dwelling ungulate endemic to the Upper Guinean forest ecosystem in West Africa, it is classified as "Endangered" by the International Union for Conservation of Nature and Natural Resources and is a Convention on International Trade in Endangered Species of Wild Flora and Fauna (CITES) Appendix II species. The smaller of the two extant hippopotamids, it is relatively uncommon in zoological facilities and private collections worldwide.